Could albumin level explain the higher mortality in hemodialysis patients with pulmonary hypertension? - Yoo, Hugo Hyung Bok (BioMed Central, 2012)
BACKGROUND: The pathogenesis of pulmonary hypertension (PH) in hemodialysis is still unclear. The aim of this study was to identify the risk factors associated with the presence of PH in chronic hemodialysis patients and to verify whether these factors might explain the highest mortality among them. METHODS: We conducted a retrospective study of hemodialysis patients who started treatment from August 2001 to October 2007 and were followed up until April 2011 in a Brazilian referral medical school. According to the results of echocardiography examination, patients were allocated in two groups: those with PH and those without PH. Clinical parameters, site and type of vascular access, bioimpedance, and laboratorial findings were compared between the groups and a logistic regression model was elaborated. Actuarial survival curves were constructed and hazard risk to death was evaluated by Cox regression analysis. RESULTS: PH > 35 mmHg was found in 23 (30.6%) of the 75 patients studied. The groups differed in extracellular water, ventricular thickness, left atrium diameter, and ventricular filling. In a univariate analysis, extracellular water was associated with PH (relative risk = 1.194; 95% CI of 1.006 – 1.416; p = 0.042); nevertheless, in a multiple model, only left atrium enlargement was independently associated with PH (relative risk =1.172; 95% CI of 1.010 – 1.359; p = 0.036). PH (hazard risk = 3.008; 95% CI of 1.285 – 7.043; p = 0.011) and age (hazard risk of 1.034 per year of age; 95% CI of 1.000 – 7.068; p = 0.047) were significantly associated with mortality in a multiple Cox regression analysis. However, when albumin was taken in account the only statistically significant association was between albumin level and mortality (hazard risk = 0.342 per g/dL; 95% CI of 0.119 – 0.984; p = 0.047) while the presence of PH lost its statistical significance (p = 0.184). Mortality was higher in patients with PH (47.8% vs 25%) who also had a statistically worse survival after the sixth year of follow up. CONCLUSIONS: PH in hemodialysis patients is associated with parameters of volume overload that sheds light on its pathophysiology. Mortality is higher in hemodialysis patients with PH and the low albumin level can explain this association.